Translation of Chinatown Pretty: Fashion and Wisdom from Chinatown's Most Stylish Seniors – from the perspective of functional equivalence theory - Su, Ying Ping (Nanyang Technological University, 2022)
This paper took an excerpt from the recently published storytelling and photography book Chinatown Pretty: Fashion and Wisdom from Chinatown’s Most Stylish Seniors as a resource for translation and the corresponding research. The textual descriptions and the accompanying bright-colored portraits document the eye-catching dressing styles and uplifting personalities of the senior immigrants from Chinatowns across North America. Taking the unique perspective from the disadvantaged group of the Chinatown elderly, the book is a celebration of color, style, and philosophical wisdom. According to its expressive nature, the translation of Chinatown Pretty as a storytelling photography involves the proficient handling of the aesthetic effects and the target texts are supposed to keep in line with the corresponding graphic illustrations. To present a faithful, intelligible, and vivid target text, under the guidance of functional equivalence, multiple strategies were flexibly adopted, including transliteration, literal translation, free translation, domestication, omission, and visualization. It is hoped that this project could provide relevant references and fresh viewpoints for translation trainees.